Effect of inulin on the pasting and retrogradation characteristics of three different crystalline starches and their interaction mechanism - Ji, Xiaolong; Wang, Zhiwen; Jin, Xueyuan; Qian, Zhenpeng; Qin, Le; Guo, Xudan; Yin, Mingsong; Liu, Yanqi (Frontiers in Nutrition, 2022)
At present, there are hardly any studies about the effect of inulin (IN) on the physicochemical properties and structures of different crystalline starches. In this study, three different crystalline starches (wheat, potato, and pea starch) were compounded with natural IN, and its pasting, retrogradation, and structural characteristics were investigated. Then, the potential mechanism of interaction between IN and starch was studied. The results showed that there were some differences in the effects of IN on the three different crystalline starch. Pasting experiments showed that the addition of IN not only increased pasting viscosity but also decreased the values of setback and breakdown. For wheat starch and pea starch, IN reduced their peak viscosity from 2,515 cP, 3,035 cP to 2,131 cP and 2,793 cP, respectively. Retrogradation experiment dates demonstrated that IN delayed gelatinization of all three starches. IN could reduce the enthalpy of gelatinization and retrogradation to varying degrees and inhibit the retrogradation of starch. Among them, it had a better inhibitory effect on potato starch. The addition of IN reduced the retrogradation rate of potato starch from 38.45 to 30.14%. Fourier-transform infrared spectroscopy and interaction force experiments results showed that IN interacted with amylose through hydrogen bonding and observed the presence of electrostatic force in the complexed system. Based on the above, experimental results speculate that the mechanism of interaction between IN and three crystalline starches was the same, and the difference in physicochemical properties was mainly related to the ratio of amylose to amylopectin in different crystalline starches. These findings could enrich the theoretical system of the IN with starch compound system and provide a solid theoretical basis for further applications.